Penerapan Hand Massage Minyak Zaitun Pada Anxietas Pasien Pre Operasi Laparatomy Di Rs Telogorejo Semarang - Siti Nur Khasanah; Rahayu Winarti (Journal of Medical Practice and Research, 2026)
Preoperative anxiety is a common psychological response among patients undergoing laparotomy and may negatively affect physiological stability and surgical outcomes. This study aimed to evaluate the effectiveness of olive oil hand massage in reducing anxiety levels among preoperative laparotomy patients at RS Telogorejo Semarang. A pre-experimental one-group pretest–posttest case study design was applied to four participants who met inclusion criteria. The intervention consisted of hand massage using olive oil administered once daily for 10 minutes over three consecutive days. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after each intervention session. The findings demonstrated a consistent decrease in HARS scores across all participants, with anxiety levels declining from moderate to mild and, in one case, to no anxiety. Improvements in physiological parameters, including blood pressure and pulse rate, were also observed. These results indicate that olive oil hand massage may serve as a simple, safe, and effective nursing intervention to alleviate preoperative anxiety. Further research with larger samples and controlled designs is recommended to strengthen the evidence base.